MOBILE BANKING FUND TRANSFER AND PROFITABILITY OF COMMERCIAL BANKS IN UGANDA. A CASE STUDY OF THE CENTENARY BANK (MAIN BRANCH) KAMPALA. A CORRELATIONAL, CROSS-SECTIONAL CASE STUDY SURVEY DESIGN. - Atukwatse , Rholine; Bakashaba, Edmand; Sendagi, Muhammad (Student's Journal of Health Research Africa, 2023)
Background. This study aims to document the relationship between mobile bank fund transfers and the profitability of Centenary Bank's main branch in Kampala, Uganda. Mobile banking refers to the act of enabling bank customers to access its services using mobile applications like phones and tablets. Mobile fund transfer refers to the transfer of funds using mobile phones. Fund transfer involves the movement of monetary funds, from one account to another. Services include performing balance checks, account transactions, payments, and other banking transactions through a mobile device such as a mobile phone which is most used in developing countries like Uganda. Centenary Bank is one of the leading commercial banks in Uganda. Therefore, this study seeks to assess the relationship between mobile bank fund transfers and the profitability of Centenary Bank's main branch in Kampala, Uganda Methodology. The study adopted a correlational, cross-sectional case study survey design. The study was correlational since it established the relationship between the study variables. It was cross-sectional since it collected data at an appointment in time for a short period and the study had no follow-up on the findings. Results. Based on the findings, there were significant positive correlations between profitability and mobile fund transfers (0.473). This means that as mobile fund transfers increase, the profitability of Centenary Bank tends to increase as well. Further, findings showed that 42.3% of the variation in profitability was explained by mobile bank fund transfers. Conclusion. Mobile banking activities, including fund transfers, have a positive impact on the profitability of Centenary Bank in Uganda. Recommendation. Centenary Bank should focus on promoting and enhancing its mobile banking transfer services to attract more customers and increase profitability. Centenary Bank should invest in robust security measures to protect customer accounts and data, ensuring the trust and confidence of their customers.